STRUKTUR POLA ASUH ANAK TENAGA KERJA WANITA DI MADURA - Heni Listiana (An-Nisa' Journal of Gender Studies, 2020)
Discussions about children and female migrant workers (TKW) are always in interesting issue. Especially, related to child care. By using data extraction techniques such as observation, interviews, and documentation, it is known that parenting children of migrant workers in Madura has formed a new structure with the emergence of a second mother. There are three types of second mothers, namely grandmother, bu de (mother's brother or sister), and sister of TKW's child. They carry out the role of mother, among them being a model of children's behavior that is easily observed and imitated, becomes an educator, becomes a consultant, and becomes a source of information. Nearly 77% of grandmothers become maternal substitutes for migrant workers' children. Grandmother is considered the right person to do childcare tasks. This structure is called the inner parenting structure. While the structure of outside parenting takes the form of community participation in child care, namely good neighbors, the attention of the village head (Klebun), and the environment of friends and schools. Pembahasan tentang anak dan Tenaga Kerja Wanita (TKW) selalu menjadi isu yang menarik. Terutama yang berkaitan dengan pola asuh anak. Dengan menggunakan teknik penggalian data berupa observasi, wawancara, dan dokumentasi diketahui bahwa pola asuh anak TKW di Madura membentuk struktur baru dengan munculnya ibu pengganti (second mother). Ada tiga jenis ibu pengganti, yaitu nenek, bu de (kakak atau adik ibu), serta kakak dari anak TKW. Mereka menjalankan peran ibu diantaranya menjadi model tingkah laku anak yang mudah diamati dan ditiru, menjadi pendidik, menjadi konsultan, dan menjadi sumber informasi. Hampir 77% nenek menjadi sosok pengganti ibu bagi anak-anak TKW. Nenek dianggap sebagai sosok yang tepat untuk melakukan tugas-tugas pengasuhan anak. Struktur ini disebut dengan struktur pola asuh dalam. Sementara struktur pola asuh luar itu berwujud peran serta masyarakat dalam pengasuhan anak yaitu tetangga yang baik, perhatian kepala desa (Klebun), dan lingkungan teman dan sekolah.